Research within the disciplines foundations for reference and library instruction - Keeran, Peggy; Levine-Clark, Michael (Rowman & Littlefield, 2014)
Research within the Disciplines is designed to help reference librarians - and students studying to become librarians - gain that deeper understanding of disciplinary differences that allows them to comfortably solve information needs rather than merely responding to questions, and practical knowledge about how to work with researchers in a library setting.